Application of Lithium Battery as Emergency Self-Traction Power Supply in Metro Vehicles - Chen XIAO; Xingxiang ZHOU; Huifa WANG (机车电传动)
The lithium battery can be used as power source under the condition of power supply failing or at the location without power supply, realizing starting in 23‰ ramp with AW3 load, completing transition or self-traction to the nearest station, and reducing rescue operation. At the current, the nickel-chromium battery is mainly used as the power source of subway vehicles, due to its volumetric, weight and discharge rate, it is difficult to be batch applied in the line. As a new type of power supply, lithium battery has many advantages in terms of volume, weight, environmental protection and discharge rate, which has a broad market prospect in the practical application field of subway vehicles.